Effect of joint traction on functional improvement and quality of life in patients with severe knee osteoarthritis - Sedigheh Sadat Naeimee; Abbas Rahimi; Mehdi Rezaee; Alireza Akbarzadeh Baghban; Khosro Khademi Kalantari; ُSomayeh Mahmoudi Aghdam (Shahid Beheshti University of Medical Sciences, 2012)
Background and aim: Osteoarthritis (OA) is the most prevalent joint disease in adults around the world and its incidence rises with age. Patients with severe knee osteoarthritis often complain of pain and severe functional disability. Most of conservative treatments used in this group of patients induce poor improvements. This study evaluated the effect of joint traction on quality of life of patients with severe knee osteoarthritis.Materials and Methods: In this clinical trial study, forty female patients with severe knee OA were randomly assigned to two following groups; common physiotherapy treatment and common physiotherapy treatment accompanied by knee distraction. Quality of life was evaluated pre- and post-treatment and also one month follow-up using the Knee injury and Osteoarthritis Outcome Score (KOOS) questionnaire.Results: Common physiotherapy treatment accompanied by knee distraction resulted in significantly better quality of life post-treatment and at 1month follow-up, compared to common physiotherapy treatment alone (P<0.01).Conclusion: Common physiotherapy treatment accompanied by knee distraction induces significant improvement in quality of life in patients with severe knee osteoarthritis compared to common physiotherapy treatment alone.